The transition to parenthood: an evaluation of low income non-married new mothers’ expectations on their relationship satisfaction - Nazarinia, Rudabeh (Kansas State University, 2009)
Previous research on the transition to parenthood has focused predominantly on middle-class White married mothers. The present research expands upon this literature by evaluating the transition of non-married, low-income, White and Women of color experiences as new mothers in their transition to parenthood. This investigation uses the Fragile Families Child Wellbeing Study. Data from 1,195 first time mothers were examined. Baseline data on mothers, as well as one-year follow-up data, were used to evaluate the New Mothers’ Relationship Satisfaction Model. This model was developed as a response to the current literature and theory as it related to low-income, people of color, and single never married women who have been overlooked or ignored in the literature. The New Mothers’ Relationship Satisfaction Model examines the effects of expectation fulfillment, father’s behavior, experience of motherhood and family support on mothers’ relationship satisfaction. The model was then used to evaluate different groups of mothers based on their race/ethnicity and then their relationship status. Findings indicated race/ethnicity and relationship status differences among several of the constructs in the New Mothers’ Relationship Satisfaction Model. For some women the experience of motherhood and father’s behavior did not have a significant effect of their relationship satisfaction as predicted by the current literature. This investigation takes the first step in providing a comparison group of new mothers that have been overlooked by much of the research in this area. This research underscores the importance of differences that exist in mothers’ transition to parenthood and points to a need for further research with more diverse populations. Social scientists interested in the transition to parenthood must focus their research and theory on a more diverse population of new mothers in order to fully understand and give meaning to this experience.
Keywords: Transition to Parenthood; Motherhood; Low Income; Relationship Satisfaction; Expectations; Psychology, Social (0451); Sociology, Ethnic and Racial Studies (0631); Sociology, Individual and Family Studies (0628)